2023
DOI: 10.33022/ijcs.v12i1.3132
|View full text |Cite
|
Sign up to set email alerts
|

Online Terrain Classification Using Neural Network for Disaster Robot Application

Abstract: A disaster robot is used for crucial rescue, observation, and exploration missions. In the case of implementing disaster robots in bad environmental situations, the robot must be equipped with appropriate sensors and good algorithms to carry out the expected movements. In this study, a neural network-based terrain classification that is applied to Raspberry using the IMU sensor as input is developed. Relatively low computational requirements can reduce the power needed to run terrain classification. By compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…An artificial neural network (ANN) was applied for the terrain classification in the research presented in [37]. The ANN was implemented on the Raspberry Pi 4B in order to process the vibration data in real time.…”
Section: Classification Methods For Terrain Type Recognitionmentioning
confidence: 99%
“…An artificial neural network (ANN) was applied for the terrain classification in the research presented in [37]. The ANN was implemented on the Raspberry Pi 4B in order to process the vibration data in real time.…”
Section: Classification Methods For Terrain Type Recognitionmentioning
confidence: 99%
“…This research results in the production of two distinct types of robots that are supplied with a variety of mechanisms. One example is the unmanned ground vehicle (UGV), which is outfitted with a variety of mechanisms for walking to identify things, arm mechanisms, and sensory capabilities that are utilized for the purposes of observation and exploration [20], [25], [26].…”
Section: Methodsmentioning
confidence: 99%
“…Exploration and observation are two of the most common uses for unmanned ground vehicles (UGV), which are purpose-built to have good ground roaming capabilities [19]. After then, UAVs are utilized for air exploration missions in a more general sense for the goals of mapping and exploration by air [20].…”
Section: Introductionmentioning
confidence: 99%
“…Gyroscopes, which measure angular velocity around one or more axes, are widely used in pattern recognition applications, such as human movement or activity recognition [32,33]. In terrain classification tasks, these sensors were mainly tested together with accelerometers [31,[34][35][36][37][38]. In a previous study, the authors of this paper showed that gyroscopes can provide significantly higher classification efficiencies than accelerometers using a frequency domain-based feature set [39].…”
Section: Introductionmentioning
confidence: 98%
“…Hasan et al applied altogether 60 different temporal, statistical and spectral features using accelerometer and gyroscope data together to classify 9 indoor surface types [37]. In [38], the components of the amplitude spectrum computed for the six channels of the IMU sensor were used together as inputs of the ANN to classify terrains into five classes, i.e., indoor floor, asphalt, grass, soil, and loose gravel.…”
Section: Introductionmentioning
confidence: 99%